Parental attachment, peer attachment, and delinquency among adolescents in Selangor, Malaysia - Lim, Jia Choon; Hasbullah @ Abdullah, Muslihah; Ahmad, Sa'odah; Wu, Shin Ling (Canadian Center of Science and Education, 2013)
This study aimed to investigate the relationships between parental attachment, peer attachment and delinquency among adolescents. 480 adolescents aged 13-17 were randomly selected from four secondary schools in Malaysia. The revised version of the Inventory of Parent and Peer Attachment (IPPA) (Armsden & Greenberg, 1987) and the Self-report Delinquency Scale (Mak, 1993) were used in this study. The results revealed significant negative relationship between father and mother attachment with ad olescents’ delinquency and significant positive relationship between peer attachments with adolescents’ delinquency. Statistically significant differences were obtained for males and females adolescents where males are more delinquent than females. Multiple regression analysis showed that gender is the strongest predictors for adolescents’ delinquency,followed by peer attachment, moth er attachment and father attachment. Practical recommendation and implementation are discussed where attachment could be included as a target for implementing intervention.